Replacement of Cable Stays in Yonghe Bridge in Tianjin, China - Hongjiang Li (Advances in Civil Engineering)
Cable replacement is one of the most important approaches for retrofitting an existing cable-stayed bridge. The Yonghe Bridge opened to traffic in 1987 and was the largest concrete cable-stayed bridge in Asia at the time. After nearly 20 years in service, its stay-cable system was completely replaced. The present paper details the key technical points of cable replacement in this bridge, including causes of replacement, cable replacement design, construction monitoring during replacement, and cable tension tuning after replacement. Based on the measurements during construction, the variation in structural condition indexes was thoroughly investigated, such as cable forces throughout the bridge, geometry profile of bridge deck, and tower horizontal displacements. The structural changes due to cable replacement were evaluated, and then, a relatively desirable scheme of cable adjustment was correspondingly put forward. The measured results showed that, influenced by the accumulated tolerances of cable forces during construction, cable replacement may often lead to a further deviation of structural condition. In this instance, cable adjustment is an effective compensation measure to improve the overall structural condition of the bridge. The practice of cable replacement in the Yonghe Bridge has provided some valuable experience or beneficial references for the similar retrofitting cases.